Paradigms of liberal education in a philosophical exploration of Daniel DeNicola - Wrońska, Katarzyna (Hybris, 2017)
The text presents thoughts of American philosopher of education Daniel R. DeNicola on liberal education contained in his book under the title „Learning to Flourishing. A Philosophical Exploration of Liberal Education”, published in 2012. He describes education realised in American Liberal Arts Colleges. Analysing paradigms in which liberal education developed and created its long and differentiated tradition, starting from the transmission of culture up to the skills of learning, DeNicola argues that none of them lost their validity. Building the thin (not thick) normative theory of liberal education aimed at the flourishing life, he states that we can still recall them all and rebuild the sense of that education. Its axiological distinctive features are freedom, autonomy, democracy and truth. DeNicola’s proposition is worth of discussing in Polish pedagogy where the prevalent equivalent of liberal education is general education. The main aims of the text are to strengthen the philosophical argument in favour of understanding general education more linked to liberal education because of its liberal elements, consequently to renew the sense of education as whole and finally to strengthen didactics philosophically.